“Identificación y control invitro de enfermedades fungosas en semillas de sacha inchi (plukenetia volubilis L.), en San Martín” - Sandoval Del Aguila, Rocio (2008)
In the San Martín region one comes motivating the production of Plukenetia volubilis L. for the production of oil and flour for which one comes selling seeds without any sanitary package for these reasons it has thought about work that has as objectives presen11y: 1) the causal agents' of the main fungous illnesses identification in seeds of Plukenetía vo/ubílis L. in San Martín. 2) to evaluate the effect of the food poisoned with fungicides in the development of the pathogens. Seeds were collected considering the Valley of the Paiwa, Pinto Recodo and San Roque of Cumbaza which were transferred to the Laboratory of Vegetable Sanity where they were carried out the respective diagnoses beginning with the camera humidity, isolation of the pathogen for the description of the biological characteristics and biometrics, patogenícidad test in seeds, neck of the root and leaves, and finally they were carried out food tests poisoned for the following mushrooms: Rhizoctonia solani, Scytalidium dimidiata. Botryodiplodia theobromae, Fusarium oxysporum, Rosellinia sp. and Fusaríum solaní that were analyzed totally at random under the design. lt has been possible to identify the following mushrooms pathogens: Rhizoctonia solani, Scytalidium dimidiata, Botryodiplodia theobromae, Fusarium oxysporum, Rosellinia sp. and Fusarium sotaní and the bacteria Erwinia caratovora. Three fungicides have been determined that have excellent control for the mushrooms that are: Methiram, TIOfanate metil + Thiram, Mancozeb.